Unsteady Rotatory Oscillations of a Vertical Cylinder In Jeffery Fluid With Ion Slip Currents and Porous Medium - Gajjela, Nagaraju; Aparna, podila (International Journal of Engineering and Technology, 2019)
The generated flow of a Jeffery fluid due to an infinite circular cylinder's rotatory oscillations is examined. Consideration is given to the effects of Magnetic field, Hall and Ion currents with porous medium. The governing partial differential equations ensuing from the linear momentum equations are determined analytically by the theory of Besselâ€™s functions. The velocity field, tangential drag force, torque and axial force acting on the cylinder are enumerated. The impacts different fluid parameters on transverse and axial velocities are investigated and presented in graph form. It is found that the longitudinal and polar velocity decreases with increasing Reynold number at a distance from the wall. The Î¸-component and z-component a velocity increase with a raise in Deborah number, also it increases with rising in Ion-slip parameter.Â NomenclatureÂ Î¡:Fluid Density:ViscosityÎ£:Electrical Conductivityð‘˜0:Permeability of the Porous MediumT:Cauchy Stress TensorI:Identity TensorS:Extra Stress TensorE:Rate of Strain:Jeffery ParametersQ0:Magnitude of OscillationsÎ’0:Angle between the Directions of Transverse Oscillation with Base VectorJ:Current DensityB:Magnetic FieldM:Magnetic ParameterRe:Reynolds NumberDa:Darcy NumberDe:Debroah Number:Ion Slip Parameter:Hall Factor,Â Â Â